ENGAGING STUDENTS IN COOPERATIVE LEARNING MODEL OF READING COURSE THROUGH NUMBERED HEAD TOGETHER - Hanik Mahmudah; Fathor Rasyid (Universitas PGRI Semarang, 2022)
The importance of a reading course in increasing students' ability to comprehend English text is critical. However, many students dislike and are uninterested in class reading activities. As a result, this study used the Numbered Head Together cooperative learning strategy to engage students in a reading course. Since this study focuses on teaching and learning activities in the classroom, it was designed as Classroom Action Research. The research was carried out in four steps. They were planning, performing, observing, and reflecting on their actions. This research was conducted in class B of the eighth grade of MTsN 1 Kediri, consisting of 39 students. The result showed that using the Numbered Head Together (NHT) strategy could help students enhance their reading comprehension skills. Furthermore, group discussions may impact students' attention and encourage them to participate in learning activities. Students were able to participate in the teaching-learning process using the Numbered Head Together (NHT) technique. They became more receptive to the teacher's explanations and collaborated with their peers in groups. They were also more engaged, enthusiastic, and confident in class activities, resulting in a livelier and more interesting classroom environment.